Aspergillus Polymerase Chain Reaction—An Update on Technical Recommendations, Clinical Applications, and Justification for Inclusion in the Second Revision of the EORTC/MSGERC Definitions of Invasive Fungal Disease. (12th March 2021) - White, P Lewis; Bretagne, Stephane; Caliendo, Angela M; Loeffler, Juergen; Patterson, Thomas F; Slavin, Monica; Wingard, John R
Abstract: Aspergillus polymerase chain reaction testing of blood and respiratory samples has recently been included in the second revision of the EORTC/MSGERC definitions for classifying invasive fungal disease. This is a result of considerable efforts to standardize methodology, the availability of commercial assays and external quality control programs, and additional clinical validation. This supporting article provides both clinical and technical justifications for its inclusion while also summarizing recent advances and likely future developments in the molecular diagnosis of invasive aspergillosis.